Reductions in body size of benthic macroinvertebrates as a precursor of the early Toarcian (Early Jurassic) extinction event in the Lusitanian Basin, Portugal. Issue 2 (29th March 2019) - Piazza, Veronica; Duarte, Luís V.; Renaudie, Johan; Aberhan, Martin
Abstract: Reduction of body size is a common response of organisms to environmental stress. Studying the early Toarcian succession in the Lusitanian Basin of Portugal, we tested whether the shell size of benthic marine communities of bivalves and brachiopods changed at and before the global, warming–related Toarcian oceanic anoxic event (T-OAE). Statistical analyses of shell size over time show that the mean shell size of communities decreased significantly before the T-OAE. This trend is distinct in brachiopods and is caused by larger-sized species becoming less abundant over time, whereas it is not significant in bivalves, suggesting a decoupled response to environmental stress. Reductions in shell size precede the decline in standardized sample-level species richness associated with the early Toarcian extinction event. Such decreases in the shell size of marine invertebrates, well before the onset of biodiversity change, suggest that reductions in body size more generally may be a precursor of a subsequent loss of species and turnover at the community level caused by climate change. Sedimentological evidence is against hypoxia as a driver of extinction and the preceding size decrease in the brachiopod fauna in the studied succession, although low oxygen levels are widely held responsible for elevated early Toarcian extinction rates globally. Reduction of mean shell size in brachiopods but stasis in bivalves is difficult to explain with ocean acidification, because experimental work shows that brachiopods can be resilient to lowered pH, albeit long-term metabolic costs and potential evolutionary adaptations are unknown. Rising early Toarcian temperatures in the Lusitanian Basin seem to be a plausible factor in both diversity decline associated with the T-OAE and the preceding reductions in mean shell size, because thermal tolerances in modern bivalves are among the highest within marine invertebrates.